PENGARUH INVESTASI, PAJAK DAERAH DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP PERTUMBUHAN EKONOMI PROVINSI RIAU - Sufnirayanti; Sri Wahyuni Zanra (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study aims to determine and examine the effect of investment. Local taxes and population on the economic growth of Riau Province in 2013-2021. The data used in this study is secondary data, in the form of time series. The data source used in this study comes from the Central Bureau of Statistics (BPS). This study uses multiple linear regression analysis and uses Statistical Tests and Classical Assumptions Tests. The data is processed using the Eviews 9 application. The results of this study indicate that investment and local taxes have a positive and significant effect on economic growth in Riau Province, while population size does not have a significant effect on economic growth in Riau Province